Strengthening the Three Pillars: Joyful Learning, Intrinsic Motivation, and Academic Achievement in Indonesian Pesantren Education - Wijiyono, Eko; Huda, Atok Miftahul; Tobroni; Widodo, Joko (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines the structural relationships among Joyful Learning, Intrinsic Motivation, and Academic Achievement within the socio-religious educational environment of an Indonesian pesantren. Grounded in contemporary motivational theory, particularly Self-Determination Theory, the research addresses the limited empirical evidence on how emotionally engaging pedagogical climates interact with internal motivational processes in faith-based boarding schools. Employing an explanatory sequential mixed-methods design, quantitative data were collected from 60 junior secondary students using validated Likert-scale instruments, followed by qualitative interviews and classroom observations to contextualize statistical findings. Data were analyzed using descriptive statistics, reliability and validity testing, normality assessment, and Pearson correlation analysis. The results reveal strong and statistically significant positive correlations between Joyful Learning and Intrinsic Motivation (r = .921, p < .001), Joyful Learning and Academic Achievement (r = .875, p < .001), and Intrinsic Motivation and Academic Achievement (r = .895, p < .001), indicating a mutually reinforcing relationship among the three constructs. Qualitative findings further demonstrate that relational mentorship, communal discipline, and value-integrated instruction within the pesantren environment strengthen students’ intrinsic engagement and meaning-making processes. The study concludes that joyful pedagogical practices can be effectively integrated within structured religious educational systems and function as catalysts for enhancing intrinsic motivation and multidimensional academic achievement. The implications of this research highlight the importance of relational pedagogy, teacher professional development, and the integration of affective-motivational indicators into assessment systems, thereby advancing culturally grounded motivational theory and educational innovation in faith-based institutions.